Solubility in pharmaceutical chemistry - Saal, Christoph; Nair, Anita (Walter de Gruyter GmbH, 2020)
This book describes the physicochemical fundamentals and biomedical principles of drug solubility. Methods to study and predict solubility in silico and in vitro are described and the role of solubility in a medicinal chemistry and pharmaceutical industry context are discussed. Approaches to modify and control solubility of a drug during the manufacturing process and of the pharmaceutical product are essential practical aspects of this book.